A Mixed-Method Study of Pre-service Teachers’ Self-efficacy in the Indonesian Teacher Professional Education Program - Tomy Kartika Putra; Ardian Pitra Satya Purnama; Suroto Rosyd Setyanto (International Journal of Pedagogy and Teacher Education, 2023)
In order to enhance the quality of national teacher selection in Indonesia, the government has introduced the Pre-service Teacher Professional Education Program (PTPE). This one-year program follows a four-year undergraduate degree and aims to produce highly qualified teachers. Teachers’ self-efficacy, which refers to the belief in one's ability to perform teaching tasks successfully, is essential in ensuring effective education. When pre-service teachers have a strong sense of efficacy during their education programs, they are more likely to be confident in assisting students in achieving learning goals. Accordingly, this study aimed to examine the pre-service teachers' self-efficacy level and identify the significant factors contributing to their development. The researchers employed an explanatory sequential mixed-method approach (Creswell, 2012) involving 37 pre-service teachers to achieve a comprehensive understanding. The study utilized the Teachers’ Sense of Efficacy Scale, the Sources of Self-Efficacy Inventory, and interviews as data collection instruments. The findings revealed two primary outcomes: 1) pre-service teachers exhibited an excessively high measure of self-efficacy, and 2) mastery experience, vicarious experience, verbal persuasion, and psychological arousal significantly contributed to pre-service teachers’ self-efficacy. The implications of this research extend to future investigation, the PTPE program, teacher educators, teacher tutors, and school leaders to support the development of pre-service teachers’ self-efficacy.